Assessment of Paramedical Specialty Students' Knowledge about Swine Flu Pandemic - Thabit, maral (Iraqi National Journal of Nursing Specialties, 2010)
Objectives: This study aims to assess the knowledge, regarding Swine Flu pandemic among a sample of paramedicalspecialty students of Medical Technology Institute (Baghdad).Methodology: The study sample included (110) male and female students, randomly selected, and data was collected bypreviously prepared questionnaire including different questions covering different clinic-epidemiological aspects of thedisease and followed by statistical analysis using simple binomial tests and average percentage of correct answers.Results: The higher percentage of correct responses regarding causative virus 83%, it is respiratory disease 83%,transmission among people through the droplets 83%, and by touching contaminated surfaces 80%, the new virus causesmore vomiting and diarrhea 68%, immune-suppressed people are more vulnerable to death 76%, economic hazards totourism and farmers dealing with pigs 80%, prevention by using disposable tissues covering nose during coughing orsneezing. The results also show that the higher percentages of wrong responses regarding the possibility of catching theswine both human and bird flu 21%, law mortality among infected pigs 42%, it is not a new disease 46%, directtransmission from human to pigs 44%, no transmission by eating properly cooked pork products 38%, the virus is notresponding to antiviral medicines 46%, there are multiple vaccines given to pigs and not for humans 44%, and average %of correct answers was 60%.Recommendations: The study recommends that additional educational courses and training should be presented for allstudents with all available methods in Swine Flu handling.